Efficacy of Oral Terbinafine with Meglumine Antimoniate/ Glucantime (Intalesional) vs Glucantime I/L alone in Treatment of Cutaneous Leishmaniasis - Naheed, Nuzhat; Rehman, Somaiya; Jabeen, Nargis; Ali, Farhad; Hassan, Yamna; Paracha, Majid (Journal of Neonatal Surgery, 2025)
Introduction: Leishmaniasis is a chronic vector-born protozoan disease, occurring in various presentations from the self-limiting, even self healing cutaneous nodular or ulcerated lesion to lifethreatning visceral disease, each caused by one of the species of the genus leishmania. It is the major health problem worldwide. It also appears to be an emerging disease in the various parts of Pakistan especially in rural areas& endemic in Bolochistan, Interior Sindh, Multan, Tribal area (refugees from Afghanistan) & western border of Pakistan. Objective: To compare the efficacy of oral terbinafine with meglumine antimoniate/(Glucantime) intralesional verses Glucantime (intralesional) alone for treatment of cutaneous Leishmaniasis. Methodology: This Randomized control trails study was carried out at the Dermatology Department Lady Reading Hospital Peshawar for duration of six months from June 2023 to November 2023. In this study a total of 102 patients were included by taking 51 in each group, using 80% efficacy of oral Terbinafine + Glucantime, 52.9% efficacy of Glucantime alone, 95% confidence level & 90% power of test (Non Probability Sampling) technique was used for sample collection. Results: Our study shows that in Group A mean age was 33 years with SD ± 3.621 and in Group B mean age was 32 years with SD ± 3.315. In Group A 68% patients were male and 32% patients were female. Where as in Group B 65% patients were male and 18(35%) patients were female. Group A (oral terbinafine 250 mg daily + Glucantime I/L) was effective in (82%) patients where as Group B (Glucantime I/L once) was effective in (60%) patients. Conclusion: Our study concludes that oral terbinafine with Glucantime (intralesional) was more effective as compare to Glucantime (intralesional) alone for treatment of cutaneous Leishmaniasis